Uncovering the Invisible Burden: A Narrative Review of the Psychological Impact of COVID-19 on Families - Fu'ady, Muh Anwar (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
The psychological issues that have emerged because of the ongoing pandemic do not manifest solely at the individual level; they also have ramifications at the familial level. The potential consequences of this pandemic include mortality, the disruption of physical contact with family members and social networks, job loss and other associated risks. A comprehensive literature search was conducted, and articles were collected from five database sources: ScienceDirect, Scopus, PubMed, EBSCOhost, and Sage Publications. The articles were published between 2020 and 2021. The findings of the research articles seek to describe systematically based on themes that have been minimally addressed by other studies, including (a) patterns of relationships between family members, (b) conflict, domestic violence, and divorce, (c) racism in the family, and (d) the impact of the death of a family member.